Honorary issue dedicated to the 80th anniversary of Professor Ihor Stasyuk - Freericks, J.K.; Shvaika, A.M. (Condensed Matter Physics, 2018)
This special issue of the “Condensed Matter Physics” journal is dedicated to Professor Ihor Stasyuk, a prominent scientist and lecturer who celebrates his 80th birthday on September 23, 2018. The articles in this collections represent different fields of the quantum many-body physics and solid state theory, where Prof. I.V. Stasyuk made significant contributions and obtained remarkable results